2004
DOI: 10.1021/ie034237q
|View full text |Cite
|
Sign up to set email alerts
|

Injection of a Liquid Spray into a Fluidized Bed:  Particle−Liquid Mixing and Impact on Fluid Coker Yields

Abstract: In industrial fluid cokers, the feedstock, consisting of heavy bituminous hydrocarbons, is atomized with steam and injected into the hot fluidized bed of coke. Good and uniform contact of the liquid droplets with the solid particles is required to provide heat for the cracking reactions while mass transfer effects are minimized. Experiments in a pilot plant coker have suggested that the initial particle/liquid mixing, in the spray jet, is rather poor. Experiments in a X-ray scanner showed that liquid droplets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 11 publications
1
52
1
Order By: Relevance
“…Both the hydrocarbon conversion efficiency and the operability of the reactor are strongly affected by the initial contact between the injected liquid and the fluidized solids. 1,2 It has been shown that improving the contact of injected liquid with fluidized particles increases the yield of valuable liquid products in both the fluid catalytic cracking process, where most of the liquid is vaporizable, and in the fluid coking process, where most of the liquid is not directly vaporizable, but must first be cracked to generate vaporizable fractions. 1,3 In the case of vaporizable liquids, liquid-solid agglomerates may or may not be formed, depending on the operating conditions, 4,5 while they always form with nonvaporizable liquids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the hydrocarbon conversion efficiency and the operability of the reactor are strongly affected by the initial contact between the injected liquid and the fluidized solids. 1,2 It has been shown that improving the contact of injected liquid with fluidized particles increases the yield of valuable liquid products in both the fluid catalytic cracking process, where most of the liquid is vaporizable, and in the fluid coking process, where most of the liquid is not directly vaporizable, but must first be cracked to generate vaporizable fractions. 1,3 In the case of vaporizable liquids, liquid-solid agglomerates may or may not be formed, depending on the operating conditions, 4,5 while they always form with nonvaporizable liquids.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It has been shown that improving the contact of injected liquid with fluidized particles increases the yield of valuable liquid products in both the fluid catalytic cracking process, where most of the liquid is vaporizable, and in the fluid coking process, where most of the liquid is not directly vaporizable, but must first be cracked to generate vaporizable fractions. 1,3 In the case of vaporizable liquids, liquid-solid agglomerates may or may not be formed, depending on the operating conditions, 4,5 while they always form with nonvaporizable liquids. 6 Bruhns et al 7 investigated the interaction between vaporizable liquid jets and fluidized solids in a pilot-scale re-actor operated at 120-180 8C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat from the hot coke particles thermally cracks the bitumen and converts it into lighter and more valuable hydrocarbon products. The thermal cracking reaction depends on the contact between bitumen and hot coke, which should occur rapidly to increase the yield of valuable condensable products and to avoid poor bed fluidity (House et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, the agglomeration techniques were only applicable in the lab, not in a commercial reactor. House et al (2004) discuss the coker application and state that the actual temperature difference of interest in a coker is 300°C (coke particles up to 650°C, bitumen feed 350°C). They developed a technique to measure how much liquid initially contacts coke particles when sprayed into a fluidized bed.…”
Section: Introductionmentioning
confidence: 99%